Phase I Study of Epigenetic Priming with Azacitidine Prior to Standard Neoadjuvant Chemotherapy for Patients with Resectable Gastric and Esophageal Adenocarcinoma: Evidence of Tumor Hypomethylation as an Indicator of Major Histopathologic Response - Schneider, Bryan J.; Shah, Manish A.; Klute, Kelsey; Ocean, Allyson; Popa, Elizabeta; Altorki, Nasser; Lieberman, Michael; Schreiner, Andrew; Yantiss, Rhonda; Christos, Paul J.; Palmer, Romae; You, Daoqi; et al. (Clinical cancer research, 2017)
Purpose: Epigenetic silencing of tumor suppressor genes (TSG) is an acquired abnormality observed in cancer and is prototypically linked to DNA methylation. We postulated that pretreatment (priming) with 5-azacitidine would increase the efficacy of chemotherapy by reactivating TSGs. This study was conducted to identify a tolerable dose of 5-azacitidine prior to EOX (epirubicin, oxaliplatin, capecitabine) neoadjuvant chemotherapy in patients with locally advanced esophageal/gastric adenocarcinoma (EGC). Experimental Design: Eligible patients had untreated, locally advanced, resectable EGC, ECOG 0–2, and adequate organ function. 5-Azacitidine (V, 75 mg/m2) was given subcutaneously for 3 (dose level, DL 1) or 5 (DL 2) days prior to each 21-day cycle of EOX (E, 50 mg/m2; O, 130 mg/m2; X, 625 mg/m2 twice daily for 21 days). Standard 3+3 methodology guided V dose escalation. DNA methylation at control and biomarker regions was measured by digital droplet, bisulfite qPCR in tumor samples collected at baseline and at resection. Results: All subjects underwent complete resection of residual tumor (R0). Three of the 12 patients (25%) achieved a surgical complete response and 5 had partial responses. The overall response rate was 67%. The most common toxicities were gastrointestinal and hematologic. Hypomethylation of biomarker genes was observed at all dose levels and trended with therapeutic response. Conclusions: Neoadjuvant VEOX was well-tolerated with significant clinical and epigenetic responses, with preliminary evidence that priming with V prior to chemotherapy may augment chemotherapy efficacy. The recommended phase II trial schedule is 5-azacitidine 75 mg/m2 for 5 days followed by EOX chemotherapy every 21 days. Clin Cancer Res; 23(11); 2673–80. ©2016 AACR.